Aspirin curcumin ester loaded biomimetic nanodrug improves cognitive deficits in a mouse model of Alzheimer's disease by regulating M1/M2 microglial polarization - Ze Li; Zhenyan Song; Chunxiang He; Jialong Fan; Wenjing Yu; Miao Yang; Ping Li; Rongsiqing Luo; Jinyong Zhou; Sijie Xu; Bin Liu; Shaowu Cheng (Materials Today Advances, 2022)
Alzheimer's disease (AD) is the most common neurodegenerative disorder, tightly related with microglia phenotypic polarization, which finally results in the stimulation of β-amyloid peptides (Aβ) and promotion of phagocytosis of neuronal synaptic structures. Thus, constructing drug system to reverse microglia phenotypic polarization is highly desired for AD therapy. In this study, we developed a nano delivery system (denoted as M@CA@GP NPs) by loading aspirin curcumin ester (CA) on the graphene oxide quantum dots (GOQDs) for AD therapy. With the modification of hybrid cell membrane, this nanoconjugate can efficiently deliver drugs to the brain and regulate the inflammatory microenvironment to improve learning and memory. Moreover, this targeting strategy exhibits the ability of regulating the microglial cell phenotype, promoting Aβ phagocytosis, and maintaining synaptic plasticity with prolonged circulation time and high biocompatibility. Taken together, our results demonstrate that the M@CA@GP NPs can alleviate glial cell activation, decrease Aβ burden, and eventually enhance cognitive functions in APPswe/PSEN1dE9 model mice. These results indicate that M@CA@GP NPs can be a promising therapeutic agent for the treatment of AD.